Committed to learn: student engagement and care in higher education. Issue 7 (10th November 2017) - Barnacle, Robyn; Dall'Alba, Gloria
ABSTRACT: Efforts to evaluate and improve student engagement have been pervasive in higher education over recent years. Critics argue, however, that troubling affinities are evident between student engagement efforts and a neoliberal agenda which emphasises accountability through performativity. Neoliberalism manifests in policies that focus on the economic benefit to individuals of higher education, rather than the broader social or intrinsic benefits. In this conceptual article, we draw on the work of Martin Heidegger and Nel Noddings in arguing that efforts aimed at promoting engagement and commitment to learn by students should include developing a capacity to care about others and things. Through the lens of care, our aim is to extend current notions of what engagement of students in their learning might look like. Challenging and supporting students entail encouraging them to take a stand on what they are learning and who they are becoming. This enriched conceptualisation has the potential to re-orient student engagement away from a narrow neoliberal agenda, while enabling students to realise the full benefits a higher education can provide.